1993
DOI: 10.1017/s0022029900027825
|View full text |Cite
|
Sign up to set email alerts
|

Yield and composition of milk from lactating mares: effect of body condition at foaling

Abstract: SummaryThe yield and composition of milk from nursing mares were studied during the first 2 months of lactation in two groups of six and five saddle mares respectively made thin or fat before foaling, then fed ad lib. post partum. Milk yield did not significantly vary with body condition (16·5 and 15·4 kg/d for fat and thin mares respectively). Milk from fat mares had a higher fat content than milk from thin mares; the reverse was found for protein. The composition of milk fat was modified: milk of fat mares w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1
9

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
3
17
1
9
Order By: Relevance
“…Our hypothesis that, under unlimited grass growth, lactating mares can be fed with grazed forages only without affecting performance of mares and foals was therefore confirmed. Doreau et al (1993) have discussed that mares fed a hay-based diet indoors equally allocated nutritional resources between milk yield to foal growth and their own body condition. Given that mare liveweight, foal growth and foal grazing duration evolved similarly between S and NS mares, we can assume that supplementation did not affect the trade-off between reserve mobilization and foal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our hypothesis that, under unlimited grass growth, lactating mares can be fed with grazed forages only without affecting performance of mares and foals was therefore confirmed. Doreau et al (1993) have discussed that mares fed a hay-based diet indoors equally allocated nutritional resources between milk yield to foal growth and their own body condition. Given that mare liveweight, foal growth and foal grazing duration evolved similarly between S and NS mares, we can assume that supplementation did not affect the trade-off between reserve mobilization and foal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Given that mare liveweight, foal growth and foal grazing duration evolved similarly between S and NS mares, we can assume that supplementation did not affect the trade-off between reserve mobilization and foal growth. Whether this would also apply to mares in poorer body condition remains to be investigated as conflicting results have been reported in the literature (Martin-Rosset and Doreau, 1980;Henneke et al, 1981;Doreau et al, 1993). Mares from different breeds could also express different resource allocation patterns, as observed in suckler cows: under limited grass growth cattle breeds with a higher milk yield potential indeed maintained milk yield to the detriment of body condition, whereas those with lower milk potential reduced milk yield but lost less liveweight (D'hour et al, 1995;Farruggia et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Dans une revue bibliographique récente (Doreau et Boulot,19S9a), l'ensemble des données disponibles avait été analysé. La présente synthèse, qui se veut complémentaire, a pour objectif de situer les particularités du lait de jument par rapport au lait d'autres espèces, en particulier à partir de résultats expérimentaux récents (Doreau et al, 1990(Doreau et al, , 1991(Doreau et al, a, 1992(Doreau et al, , 1993.…”
Section: Introductionunclassified
“…Ruegg & Milton, 6 and Domecq et al 7 reported no significant effect of BCS at calving on subsequent milk production, while Markusfeld et al 8 and Roche et al 9 reported the contrary to the previous findings. Singh et al 10 and Lents et al 11 stated that BCS did not influence fat, SNF and specific gravity of milk, while Doreau et al 12 reported high milk fat in fatty animals. However, negative correlation between BCS and milk yield, fat and SNF was observed by Mustaq & Quereshi.…”
mentioning
confidence: 99%